Liquid crystalline epoxy thermoset with azomethine mesogen - Mija, A.; Cascaval, C. N. (Polimery, 2022)
This work is a continuation of our earlier investigations on the liquid crystalline epoxy resins containing azomethine as mesogen group. The present study concerns the curing reaction of an azomethine epoxy monomer, namely, N,N'-(1,4-phenylenedimethylidyne)-di-4-(2,3-epoxypropoxy) aniline (AZ-2) in the presence of 2-amino-biphenyl (2-ABPh), used as a curing agent. The crosslinking reaction, the phase transitions and the thermal properties of the synthesized thermoset were monitored by differential scanning calorimetry (DSC), polarized optical microscopy and wide-angle X-ray scattering (WAXS). The main thermal transitions observed by DSC in dynamic conditions are due to both melting of the mixture components and the crosslinking reaction. The reaction of AZ-2 monomer with 2-ABPh takes place in the temperature range from 184 to 278°C, and the process is accompanied with homopolymerization of the epoxy groups. The microscopic technique revealed the appearance of a smectic type mesophase, the result being confirmed by WAXS measurements.